Bioremediation of artificially contaminated soil with petroleum using animal waste: cow and poultry dung. Issue 1 (1st January 2020) - Olawale, O.; Obayomi, K. S.; Dahunsi, S. O.; Folarin, O.
Abstract: This research investigated the use of cow dung (CD), poultry dung (PD) and cow dung/poultry dung for the bioremediation of artificially contaminated soil with petrol using response surface methodology. The application of cow dung and poultry dung to the contaminated soil was done through a statistical approach and the Box–Behnken design of experiment was adopted using design expert 6.0.8 software. The percentage of petrol removed was used as the response to assess the biodegradation. Experimental results revealed 84–96% for petrol degraded. Analysis of results showed that the quadratic model fitted best with R 2 value of 95.85% of petrol removed and the results were also significant at probability values of 0.0487, 0.0114, 0.0113, 0.0001, 0.0016, 0.0234 and 0.003, respectively, were less than 0.05. The optimum process conditions obtained were 2.54 g CD, 3.34 g PD and 2.41 g CD/PD for the percentage of petrol removed and it gave a percentage of petrol removed as 99% from day 5 and then attained equilibrium. A graph of days vs percentage of petrol removed was plotted. Furthermore, biochemical test was carried out on the soil and three of the microorganisms were used also for the bioremediation. The microorganisms are Bacillus, Aspergillus and E. coli, respectively. The best degrader of petrol from the microorganism was Bacillus in which the percentage of petrol removed was 92%. This indicates that augmenting artificially contaminated soil with petrol with cow dung and poultry dung will enhance remediation and restoration of the polluted soil.